A revamped rat reference genome improves the discovery of genetic diversity in laboratory rats - de Jong, Tristan V; Pan, Yanchao; Rastas, Pasi; Munro, Daniel; Tutaj, Monika; Akil, Huda; Benner, Chris; Chen, Denghui; Chitre, Apurva S; Chow, William; Colonna, Vincenza; Dalgard, Clifton L; et al. (bioRxiv, 2023)
The seventh iteration of the reference genome assembly for Rattus norvegicus-mRatBN7.2-corrects numerous misplaced segments and reduces base-level errors by approximately 9-fold and increases contiguity by 290-fold compared to its predecessor. Gene annotations are now more complete, significantly improving the mapping precision of genomic, transcriptomic, and proteomics data sets. We jointly analyzed 163 short-read whole genome sequencing datasets representing 120 laboratory rat strains and substrains using mRatBN7.2. We defined ~20.0 million sequence variations, of which 18.7 thousand are predicted to potentially impact the function of 6,677 genes. We also generated a new rat genetic map from 1,893 heterogeneous stock rats and annotated transcription start sites and alternative polyadenylation sites. The mRatBN7.2 assembly, along with the extensive analysis of genomic variations among rat strains, enhances our understanding of the rat genome, providing researchers with an expanded resource for studies involving rats.
Keywords: Phylogenetic Tree; Recombinant Inbred; Rat; Reference Genome; Heterogeneous Stock; Hybrid Rat Diversity Panel; Genetic Map; Rnor_6.0; mRatBN7.2; Inbred Strains